2021
DOI: 10.3390/jpm11080801
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Laser Doppler Flowmetry, as a Diagnostic Tool in Assessing Pulp Vitality of Traumatised Teeth: A Split Mouth Clinical Study

Abstract: Aim: This study aimed to evaluate the efficacy of laser Doppler flowmetry (LDF) in determining the changes in the pulpal blood flow (PBF) during post-traumatic period of the traumatised permanent teeth. Methods: 88 teeth of 44 patients (mean age 10.30 ± 2.38) were recruited according to the eligibility criteria and divided into two groups: test group (44 traumatised teeth) and control group (44 sound and healthy teeth). The measurement of PBF was performed, using a LDF monitor. Results: The analysis of the LDF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…On the other hand, some studies found LDF to be an accurate vitality testing method to assess the pulpal vascularity changes of human primary teeth [ 35 ], while others reported the opposite [ 37 ]. Moreover, the LDF procedure is a lengthy and more sensitive technique compared to conventional pulp vitality tests [ 9 , 38 ], which makes it improper for routine use in children; however, it is reserved for research purposes and particular clinical situations such as trauma to the anterior teeth [ 39 ] or “dens invaginatus” [ 40 ]. In our study, LDF testing was limited to T0 and T1 (tests at T2 and T3 are not completed) due to the rapid growth of the canine specimens in the two-week time span of the study, which negatively impacted the adaptation of the stabilizing silicone impression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies found LDF to be an accurate vitality testing method to assess the pulpal vascularity changes of human primary teeth [ 35 ], while others reported the opposite [ 37 ]. Moreover, the LDF procedure is a lengthy and more sensitive technique compared to conventional pulp vitality tests [ 9 , 38 ], which makes it improper for routine use in children; however, it is reserved for research purposes and particular clinical situations such as trauma to the anterior teeth [ 39 ] or “dens invaginatus” [ 40 ]. In our study, LDF testing was limited to T0 and T1 (tests at T2 and T3 are not completed) due to the rapid growth of the canine specimens in the two-week time span of the study, which negatively impacted the adaptation of the stabilizing silicone impression.…”
Section: Discussionmentioning
confidence: 99%
“…Gazelius et al [29] first used LDPM to measure blood flow in dental pulp tissue and assess the physiological status of the pulp. Belcheva et al [30], to monitor changes in pulp blood flow (PBF) after permanent tooth trauma, randomly divided 88 teeth from 44 patients into an experimental group (44 traumatized teeth) and a control group (44 healthy teeth). They used LDF to measure PBF values in both groups.…”
Section: Blood Perfusion Monitoringmentioning
confidence: 99%
“…Furthermore, there are conflicting results reported in the literature. In a study on traumatized teeth, Belcheva et al concluded that LDF is a useful monitoring tool for the revascularization of traumatized teeth and a reliable objective diagnostic indicator of pulp vitality [ 54 ]. A case report revealed the successful follow-up of pulpal status using LDF and EPT after vital pulp therapy performed in a dens invaginatus [ 55 ].…”
Section: Vitality Pulp Testsmentioning
confidence: 99%